Penile Fracture: Experience from a Third World Country - Rajandeep Singh Bali; Arshad Rashid; Majid Mushtaque; Shakeeb Nabi; Sajad Ahmad Thakur; Rouf Ahmad Bhat (Advances in Urology)
Aim. To ascertain the clinical presentation, commonest age group affected, and treatment of patients diagnosed to have penis fracture. Materials and Methods. We performed a retrospective study carried at a tertiary care hospital from January 2005 to January 2011. All the 36 patients diagnosed to have penile fracture were enrolled in the study group. The diagnosis was made based on the clinical findings in the patients. All, except two patients, were managed by a standard surgical procedure, same for all the patients, on the day of presentation to the hospital. All the data pertaining to the presentation, management, and followup of these patients were studied and scrutinized thoroughly. Results. Thirty-four patients were operated while 2 refused surgery. Most of our patients were between 16 and 30 years (55.6%) of age. The commonest presenting complaints were penile swelling and detumescence during sexual intercourse or an erection. All except two of our patients were managed with immediate surgical repair which had excellent results even in the presence of associated urethral injury. Conclusion. Fracture of the penis is a surgical emergency which can be best managed by immediate surgical repair with excellent results even in the presence of urethral injury.